Prevalance and Molecular Characterisation of Giardia duodenalis Infection on Goatkids Southeast Turkey - SAYIN IPEK, Duygu Neval (MAS Journal of Applied Sciences, 2023)
Giardia duodenalis, a common intestinal protozoan, affects humans and mammals, including goats. This study investigated the prevalence and genetic characteristics of G. duodenalis in goat kids in southeastern Turkey. Fecal samples were collected from 112 goatkids, and microscopic and molecular analyses were conducted. A direct immunofluorescence test was used to confirm the presence of G. duodenalis cysts in collected fecal samples. Molecular confirmation was done with Polymerase chain reaction (PCR) using G. duodenalis SSU-rRNA. The secondary PCR products of all positive samples were sequenced in one direction on an automated sequencer. Nucleotide sequence analysis was performed by BLAST alignment using the National Center for Biotechnology Information database. Out of 112 fecal samples, 28.57% tested positive for G. duodenalis. Genotyping revealed that all positive samples belonged to assemblage E, a genotype previously identified in various domestic animals and even humans, suggesting zoonotic potential. These findings emphasize the significance of G. duodenalis in goatkids for both animal and human health and highlight the need for further epidemiological studies to assess its zoonotic potential in different regions of Turkey.